Reorientation of The Arabic Language Curriculum for Secondary Education in The Endemic Era - Mukmin Mukmin; Nurul Hidayah; Siti Marpuah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The role of secondary education in the 21st century is increasingly vital for preparing students who will enter higher education and responding to the learning transition due to the Covid-19 pandemic. This form of response is by reviewing the orientation of the Arabic language curriculum in secondary education in South Sumatera. So, this research aims to analyze the reorientation of the Arabic language curriculum in secondary education in South Sumatera. The research method used by researchers is a case study method with a multisite design. Researchers collected qualitative data by interviews, observation and documentation in each place, then proceed with generalizations from the data collection results, and then conclusions are drawn as research data findings. The results of this research show that both schools had efforts to direct students to be active in learning Arabic, namely by changing books and adding books that support ongoing Arabic language learning activities, the schools also provide a conducive environment for the learning process. To convey this material, the teacher also chooses a student-centered method, hoping that students will always be active and that Arabic will not only end up as a language of study. As a measure of achievement, teachers have maximized the provision of media-based assignments and exam questions, even though the measurement techniques carried out by teachers have only focused on cognitive measurements, and have not yet entered into the affective and psychomotor domains.